A legitimidade ativa do Ministério Público na ação de improbidade administrativa - Zoboli, Fernanda Henriques Gonçalves (2023)
The present work is dedicated to the active legitimacy in the action of administrative improbity. Initially, the text focuses on the Public Ministry, considering that this was the only legitimate asset provided for by the Administrative Improbity Law, after the amendments to Law nº 14.230/21. Then, the history of the protection of administrative probity in Brazil and the sanctions imposed by the Constitution and the Law in cases of improper acts are practiced is studied. In the sequence, it enters into the research of Administrative Law to Sanction. Afterwards, the legal nature of the action of administrative improbity is addressed and the analysis of the civil inquiry follows. Finally, we arrive at the central theme referring to the constitutionality of the exclusive active legitimacy of the Public Prosecutor's Office for the filing of the action of administrative improbity and the treatment given by the doctrine and by the jurisprudence to the theme